Caulobacter Strains Code for Novel Restriction Endonucleases That Protect Them from Bacteriophage Infections - Ian Sisto; Bert Ely (Viruses)
Bacteriophages grown on Caulobacter vibrioides strain CB15 have reduced plating efficiency on other Caulobacter strains. To determine the cause of this reduced plating efficiency, we performed a series of experiments that demonstrated that the reduced plating efficiency is due to a novel set of restriction and modification (RM) enzymes that are present in most of the Caulobacter strains that we tested. We then demonstrated that one of these RM systems recognizes the nucleotide sequence 5′-ATNNAT-3′. A careful inspection of the genome nucleotide sequences of each of the strains revealed that the genes coding for these RM enzymes have not been annotated or identified, suggesting that the proteins may differ from the common types of bacterial restriction and modification enzymes. In addition, the host strain NA1000 contains a 26 kb mobile element that provides resistance to incoming phages.